Teaching a learning disabled child a case study - Farretta, Patricia Anne 1950-; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1977)
This study was an experiment in teaching a learning disabled child using the clinical teaching approach and the prescriptive teaching method. The subject involved was a child diagnosed as learning disabled through diagnostic findings.
Vita.
Thesis (Master of Arts in Teaching Special Education)--University of the Philippines, Diliman
Keywords: Children with disabilities -- Education -- Philippines; Learning ability -- Testing; Special education -- Philippines